Process of infection with bacteriophage phi X174 XLI. Synthesis of defective phi X particles at 15 degrees C. - Espejo, R T (1976)
At 15 degrees C, phi X174-infected cells make single-stranded viral DNA fragments, varying in size from 0.2 to 0.9 times that of phi X DNA. In non-deproteinized lysates, this single-stranded DNA is found associated with proteins in particles sedimenting heterogeneously with an S20, w average of 80 to 90S. These particles do not differ appreciably from mature virus in polypeptide composition. Chase experiments, at 37 degrees C, of the label incorporated into this DNA at 15 degrees C suggest that both the single-stranded DNA fragments and the 80 to 90S particles are not precursors of virions but are defective end products.